Conditional gene regulation models demonstrate a pro‐proliferative role for growth hormone receptor in prostate cancer. Issue 5 (22nd December 2022) - Unterberger, Christopher J.; McIlwain, Sean J.; Tsourkas, Philippos K.; Maklakova, Vilena I.; Prince, Jordyn L.; Onesti, Abigail; Hu, Rong; Kopchick, John J.; Swanson, Steven M.; Marker, Paul C.
Abstract: Background: Humans with inactivating mutations in growth hormone receptor (GHR) have lower rates of cancer, including prostate cancer. Similarly, mice with inactivating Ghr mutations are protected from prostatic intraepithelial neoplasia in the C3(1)/TAg prostate cancer model. However, gaps in clinical relevance in those models persist. The current study addresses these gaps and the ongoing role of Ghr in prostate cancer using loss‐of‐function and gain‐of‐function models. Methods: Conditional Ghr inactivation was achieved in the C3(1)/TAg model by employing a tamoxifen‐inducible Cre and a prostate‐specific Cre. In parallel, a transgenic GH antagonist was also used. Pathology, proliferation, and gene expression of 6‐month old mouse prostates were assessed. Analysis of The Cancer Genome Atlas data was conducted to identify GHR overexpression in a subset of human prostate cancers. Ghr overexpression was modeled in PTEN‐P2 and TRAMP‐C2 mouse prostate cancer cells using stable transfectants. The growth, proliferation, and gene expression effects of Ghr overexpression was assessed in vitro and in vivo. Results: Loss‐of‐function for Ghr globally or in prostatic epithelial cells reduced proliferation and stratification of the prostatic epithelium in the C3(1)/TAg model. Genes and gene sets involved in the immune system and tumorigenesis, for example, were dysregulated upon global Ghr disruption. Analysis of The Cancer Genome Atlas revealed higher GHR expression in human prostate cancers with ERG‐fusion genes or ETV1‐fusion genes. Modeling the GHR overexpression observed in these human prostate cancers by overexpressing Ghr in mouse prostate cancer cells with mutant Pten or T‐antigen driver genes increased proliferation of prostate cancer cells in vitro and in vivo. Ghr overexpression regulated the expression of multiple genes oppositely to Ghr loss‐of‐function models. Conclusions: Loss‐of‐function and gain‐of‐function Ghr models, including prostatic epithelial cell specific alterations in Ghr, altered proliferation, and gene expression. These data suggest that changes in GHR activity in human prostatic epithelial cells play a role in proliferation and gene regulation in prostate cancer, suggesting the potential for disrupting GH signaling, for example by the FDA approved GH antagonist pegvisomant, may be beneficial in treating prostate cancer.